2014
DOI: 10.1590/sajs.2014/20130280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atmospheric trace metals in the western Bushveld Igneous Complex, South Africa

Abstract: Trace metal species emitted into the atmosphere from natural and anthropogenic sources can cause various health-related and environmental problems. Limited data exist for atmospheric trace metal concentrations in South Africa, which has the largest industrialised economy in Africa, with significant mining and metallurgical activities. A large fraction of these mineral assets is concentrated in the Bushveld Igneous Complex, with the western limb being the most exploited. To partially address this knowledge gap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Therefore, concentrations presented for these species are most likely to be an overestimate due to the precautionary assumption. The annual mean PM 10 trace metal concentrations at Welgegund (Table 1) were typically lower than previous studies conducted in South Africa (Kgabi, 2006;Kleynhans, 2008;Van Zyl et al, 2014). This is expected, as Welgegund is a regional background location and the previous studies were conducted at sites within two priority areas, as mentioned previously.…”
Section: Contextualisation Of Atmospheric Trace Metal Concentrationssupporting
confidence: 51%
See 4 more Smart Citations
“…Therefore, concentrations presented for these species are most likely to be an overestimate due to the precautionary assumption. The annual mean PM 10 trace metal concentrations at Welgegund (Table 1) were typically lower than previous studies conducted in South Africa (Kgabi, 2006;Kleynhans, 2008;Van Zyl et al, 2014). This is expected, as Welgegund is a regional background location and the previous studies were conducted at sites within two priority areas, as mentioned previously.…”
Section: Contextualisation Of Atmospheric Trace Metal Concentrationssupporting
confidence: 51%
“…The presence of these trace metal species predominantly in the smaller size fractions, especially considering the relatively large contribution in the PM 1 size fractions, indicates the influence of industrial (high-temperature) activities on air masses measured at Welgegund. Trace metal concentrations measured at Marikana, situated within the western Bushveld Igneous Complex, indicated that Cr, Mn, V, Zn and Ni occurred almost exclusively in the PM 2.5 size fraction, with no contribution by coarser particles (Van Zyl et al, 2014). The large influence of wind-blown dust on trace metal concentrations determined at Welgegund is also reflected, with approximately 30 % of most of these trace metals being present in the PM 2.5-10 size fraction.…”
Section: Size-resolved Concentrations and Size Distribution Of Trace mentioning
confidence: 92%
See 3 more Smart Citations